PENGARUH INTENSITAS PENGGUNAAN TIKTOK TERHADAP PERILAKU IMPULSIVE BUYING PADA MAHASISWA DI KOTA MALANG - J. A, Jasmine Hayumarietta; Farha, Uzma Makkiya; Salsabila, Widya Nurieke; Kusuma, Yumna Rania (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2024)
Social media has become an important part of everyday life,especially among teenagers. One of the most widely usedapplications is TikTok. According to data, TikTok users aredominated by teenagers aged 18-24 years and the time spentaccessing TikTok is more than one hour every day. TikTok canbe used for entertainment, education and even marketing. Thisresearch aims to determine the frequency of intensity of TikTokuse, the frequency of impulsive buying behavior, and theinfluence of the intensity of TikTok use on impulsive buyingbehavior among students in the city of Malang. The method usedis a quantitative approach and data is collected by spreading ascale that measures the intensity of TikTok use and impulsivebuying behavior using Google forms. The results show that theintensity of TikTok use is moderate and impulsive buyingbehavior is low. Meanwhile, the use of TikTok has an influenceon impulsive buying behavior among students in Malang Cityby 9.7%. The solution that can be given is to increase individualself-control.